Asset allocation and strategic role of Danantara Indonesia sovereign wealth fund - Rosmi Yanti; Moh Yudi Mahadianto; Nurul Fikri Rahmah Shafana (Jurnal Ekonomi Indonesia, 2026)
This article takes a look at what makes a sovereign wealth fund successful, with a focus on where the recently established Daya Anagata Nusantara in Indonesia fits into the bigger picture of international and ASEAN investment frameworks. This study employs a quantitative methodology, examining a statistical sample of 25 observations extracted from the annual reports of five prominent sovereign wealth funds: Norway's GPFG, the Abu Dhabi Investment Authority, Singapore's GIC, China Investment Corporation, and Malaysia's Khazanah Nasional, from 2020 to 2024. Danantara is studied using a SWOT framework, descriptive statistics, correlation analysis, and principal component analysis. However real estate and renewable energy may demonstrate restricted or maybe negative short-term effects, The data indicate that market value and stock allocations are the primary factors influencing the long-term success of sovereign wealth funds. A comparative analysis reveals significant differences in transparency and governance, with Norway's GPFG serving as a benchmark worldwide. The implications indicate that Danantara ought to focus on equitable growth, create strong governance frameworks, and strategically align itself as a digitally-focused sovereign wealth fund to improve investment diplomacy within ASEAN.